Gene expression profiles during short-term heat stress; branching vs. massive Scleractinian corals of the Red Sea - Keren Maor-Landaw; Oren Levy (PeerJ, 2016)
It is well-established that there is a hierarchy of susceptibilities amongst coral genera during heat-stress. However, molecular mechanisms governing these differences are still poorly understood. Here we explored if specific corals possessing different morphologies and different susceptibilities to heat stress may manifest varied gene expression patterns. We examined expression patterns of seven genes in the branching corals Stylophora pistillata and Acropora eurystoma and additionally in the massive robust coral, Porites sp. The tested genes are representatives of key cellular processes occurring during heat-stress in Cnidaria: oxidative stress, ER stress, energy metabolism, DNA repair and apoptosis. Varied response to the heat-stress, in terms of visual coral paling, algal maximum quantum yield and host gene expression was evident in the different growth forms. The two branching corals exhibited similar overall responses that differed from that of the massive coral. A. eurystoma that is considered as a susceptible species did not bleach in our experiment, but tissue sloughing was evident at 34 °C. Interestingly, in this species redox regulation genes were up-regulated at the very onset of the thermal challenge. In S. pistillata, bleaching was evident at 34 °C and most of the stress markers were already up-regulated at 32 °C, either remaining highly expressed or decreasing when temperatures reached 34 °C. The massive Porites species displayed severe bleaching at 32 °C but stress marker genes were only significantly elevated at 34 °C. We postulate that by expelling the algal symbionts from Porites tissues, oxidation damages are reduced and stress genes are activated only at a progressed stage. The differential gene expression responses exhibited here can be correlated with the literature well-documented hierarchy of susceptibilities amongst coral morphologies and genera in Eilat’s coral reef.